Effects of pre-exposure to low temperatures on the growth of tropical forage legumes submitted to chilling-stress - Goldfarb, Maria Cristina; Saibro, João Carlos de (Pesquisa Agropecuaria Brasileira, 1996)
This study was carried out to evaluate in growth chambers the behaviour of tropical forage legumes under chilling-stress conditions. A hypothesis was made by which low temperatures (15 / 10 ºC day/night) applied just before a cold stress (15 / 2 ºC) period would influence the development of plant cold-hardening. Leucaena pulverulenta Sel 22, L. leucocephala cv. Perú and cv. Cunningham were studied. During seven days, plants were either submitted to a 15/10 ºC day/ night regime, or maintained under 30/20 ºC, as a control. To promote plant growth and recovery after the stress, a 30/20 ºC regime was used. The dry matter daily growth rate was determined. Sel 22 and cv. Cunningham showed more cold tolerance than cv. Perú. Legume recovery after stress was greater under the cold-hardening induction condition. The greatest sensibility was shown when plants suffered stress during active growth. Cv. Cunningham and Sel 22 exhibited more cold-hardening than cv. Perú.
Keywords: Leucaena leucocephala; L. pulverulenta; plant growth; dry matter